ELEKTRONIK REFLEKSI DIRI (E-RD) SEBAGAI SARANA MENINGKATKAN PEMAHAMAN MATERI TEKS ULASAN MATA PELAJARAN BAHASA INDONESIA SISWA KELAS VIII SMP BATIK PROGRAM KHUSUS SURAKARTA DI MASA PERPANJANGAN PSBB - Rizka Rahma Pradana Pradana (Jurnal Analisis Pendidikan Sosial, 2023)
This study aims to determine how to improve the understanding of text material reviews using electronic self-reflection (e-RD). This research includes classroom action research with the subject of class VIIIA with 20 students of SMP Batik Surakarta Special Program. This study used two cycles with two meetings consisting of four stages including planning, implementing, observing, and reflecting. The implementation of student learning in this study was carried out online. Based on the results of research on electronic self-reflection (e-RD), it can improve material understanding as evidenced by the first cycle, it was obtained that the average student completed 57.5% of 20 students, while the second cycle got an average score of 82.5%. So that the results of observation of electronic self-reflection optimization (e-RD) by 25% can increase students' understanding of the material presented by the teacher.